The effect of midwife training in strengthening the mental health of postpartum mother - Sumarni Sumarni; Shinta Prawitasari; ika putri (Journal of Community Empowerment for Health, 2020)
Most midwives in the Cangkringan Community Health Center and Pakem Health Center are not familiar with the symptoms of blues depression. Data shows that in Cangkringan Community Health Center, blues depression occurs 60%, 2 cases due to delayed treatment (the mother almost killed her baby). In the Pakem Health Center area, blues depression occurs at 48.1%, 2 cases experience postpartum depression due to late handling, 1 mother tries suicide. If blues depression is not handled properly and immediately, it would cause postpartum depression, which can cause the worst complications, namely postpartum psychosis. One effort to overcome this is by providing midwife training on early detection and handling of blues depression accompanied by social support. Social support and spiritual training held in six steps (once in a week a during 1,5 months. The tools in this research consist of early detection for blues depression module, social support and spiritual for blues depression prevention, Edinburgh Postnatal Depression Scale questionnaire, knowledge, and skill of blues depression early detection module and social support and spiritual questionnaire. The method in this research use presentation, discussion, role-play, practice, association, and implementation. Analyze data using the quantitative descriptive approach. Research subjects are consist of 47 midwives in the Cangkringan Community Health Center and Pakem Health Center Area and 67 postpartum women in the Cangkringan Community Health Center and Pakem Health Center Area. The results show the average value of blues depression prevention knowledge is 43.45 after training increases 85,20. The average value of blues depression early detection knowledge is 57.56; after training increase 91,27. The average value of Blues depression prevention skills is 36.45, after training increase 80,25, and the average value of blues depression early detection is 51.30, after training increase 90,20. Blues Depression in postpartum women in the Cangkringan and Pakem health centers is 57%. Changes in the average value of knowledge about blues depression control before training were 43.45% to 85.20% after training increased 41.75. Changes in the average value of skills regarding prevention and early detection of blues depression before training amounted to 36.45 to 80.85 after training increased by 44.40. The whole series of training midwives in the Cangkringan Community Health Center and Pakem Health Center Area can improve the knowledge and skills of midwives to overcome blues depression in postpartum women, reduce the incidence of blues depression in postpartum women, and reduce maternal and child mortality due to postpartum mental disorders.